THE ROLE OF SOCIAL MEDIA IN INCREASING MARKET SHARE OF MSME PRODUCTS IN PEMATANGSIANTAR CITY - Sherly Sherly; Fitria Halim; Acai Sudirman (JURNAL MANAJEMEN DAN BISNIS, 2020)
The increase in product market share cannot be separated from the connectivity of the marketing system and media used. Marketing channels play an important role in increasing sales both in the short and long term. This study aimed to determine the role of social media in increasing the market share of MSME products in Pematangsiantar City. The research design used a literature study and field study models using a qualitative approach with a one-shot model. The research location was in 8 districts in Pematangsiantar City. The population in this study were MSME players scattered in 8 districts in Pematangsiantar City. The samples were collected using a non-probability sampling technique with purposive sampling technique, so that a total sample size of 240 respondents were obtained. Moreover, the data analysis technique used in this study was data analysis with a data reduction model that was obtained from data collection and data display. The results of this study concluded that the use of social media was very dominant in MSME players in the micro sector and Instagram was one type of social media that was often used. Furthermore, the results of the study also suggested that the time factor was the basis for MSME players using social media as a medium for promoting their products.